Spectral characterization of Paspalum notatum under different nitrogen fertilization - Fonseca, Eliana Lima da; Rosa, Luís Mauro Gonçalves; Fontana, Denise Cybis (Pesquisa Agropecuaria Brasileira, 2002)
Remote sensing techniques using spectral properties of canopies may be used to monitor vegetation growth conditions throughout the year, as well as to estimate the yield of different species. However, before these techniques can be used, it is necessary to establish the spectral properties of each of the different species which make up the landscape. The objective of this study was to characterize the spectral reflectance of Paspalum notatum Flügge var. notatum, growing on different levels of nitrogen fertilization. A field experiment was carried out at the Agronomic Experimental Station of Universidade Federal do Rio Grande do Sul, Brazil (30º5'22'' S, 51º39''8'' W), using a portable spectroradiometer, on plots with P. notatum fertilized with 0, 200 and 400 kg ha-1 of nitrogen. The spectral response of P. notatum changed in response to increases in biomass caused by the different levels of nitrogen fertilization used. Increases in biomass resulted in a reduction in reflectance on the visible portion of the spectrum and an increase on the infrared portion, indicating, therefore, that the reflectance analysis is a good indicator of plant canopy status.